A new species of Ichthyurus (Coleoptera: Cantharidae: Chauliognathinae) preying on tasar silkworm, Antheraea mylitta (Drury) from India - Reddy, Karthik M.; Biffi, Gabriel; Gadad, Hanamant; Bhagat, Ampi; Chowdary, N. B.; Sushil, S. N.; Sreedevi, Kolla (Zootaxa, 2025)
The Ichthyurini are a diverse and widespread tribe of Chauliognathinae (Cantharidae) comprising nearly 300 species, but, so far, their biological data are scarce, and nothing is known about their behaviour and feeding habits. Here, we describe and illustrate a new species, Ichthyurus antheraeanus Sreedevi, Reddy, and Biffi, sp. nov. from Jharkhand, India, and report for the first time the predatory behaviour of a species in the tribe. Males and females of I. antheraeanus sp. nov. were found preying on early instar larvae of the tasar silkmoth, Antheraea mylitta (Drury, 1773) (Lepidoptera: Saturniidae). Detailed descriptions and photographic illustrations of adult habitus and genitalia of both sexes of the species as well as their COI mtDNA barcode are provided. The potential harm that I. antheraeanus sp. nov. may have on the tasar silk production in India is discussed.